Socio-Demographic Aspects of Selected Menstrual Hygienic Practices Among Adolescent School Girls in Pondicherry - Abhijit V Boratne; Shib Sekhar Datta; Karthiga Vijaykumar; Suba Joice Y; Zile Singh (Medsci Publications, 2016)
Background: The menstrual hygiene is one of the important as- pects in adolescent health which is influenced by different socio- demographic factors. Objective: To study the socio-demographic aspects of selected menstrual hygienic practices among adolescent school girls in Pondicherry. Material & methods: The present cross sectional study was carried out among 371 adolescent girls from four selected schools who at- tained menarche. They were interviewed after obtaining written informed consent from their parents. To study the effect of socio- demographic characteristics on critical menstrual hygienic prac- tices, Odds ratios (ORs) were calculated. Results: Use of sanitary pad is not associated with mother's educa- tion & occupation as well as caste and religion. Girls from rural school (OR: 0.50; 95% CI: 0.29-0.88) were found to use less sanitary pads than their counterparts. The girls of illiterate mothers & backward castes were more likely to wash their genitalia with soap and water than girls with literate mothers and from forward castes. Conclusion: The place of residence has emerged as a significant factor for adolescent school girls to practice selected menstrual hy- gienic practices such as usage of sanitary pads during menstruation.